Production potential of rangeland grasses in association with stylosanthes (Stylosanthes hamata) - HOSMANI, M M; BABALAD, H B; GANAJAXI, GANAJAXI (The Indian Journal of Agricultural Sciences, 2013)
A field trial was conducted during 1994-95 and 1995-96 at Dharwad to evaluate the production potential of mixedsward of stylosanthes (Stylosanthrs hamata (L.) Taubert and Stylosanthes scabra.T. Vagel) association with 8 rangeland grasses. The green forage yield of stylosanthes species varied during both the years and was significantly higherin Stylosanthes hamata than in Stylosanthes scabra. Among the range grasses Brachiaria decumense staff. (signal),Cenchrus ciliaris (L.) (anjan) gave higher green forage yield over other during both the years. Total green forage yieldof mixed swards with stylosanthes when grown in association with anjan followed by signal was significantly higherthan sole grasses. The dry fodder yield of mixed sward was significantly higher with panicum, anjan and signalcompared with other grasses. Growing stylosanthes in association with anjan was superior over the other combinations.